Institutional Governance and Investment Licensing Reform in Indonesia’s Free Trade Zones: A Case Study of Tanjungpinang - Ade Masniary; Rumzi Samin; Edy Akhyari (Universitas 17 Agustus 1945 Samarinda, 2026)
The Free Trade Zone (FTZ) policy was established to stimulate regional economic growth through investment promotion, trade facilitation, fiscal incentives, and simplified licensing procedures. Despite possessing strategic geographical advantages, the implementation of the FTZ policy in Tanjungpinang has not yet achieved its intended objectives. This study examines institutional fragmentation in investment licensing governance within the Tanjungpinang FTZ and analyzes its implications for investment service effectiveness. A qualitative case study approach was employed, utilizing in-depth interviews, document analysis, and literature review. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, consisting of data reduction, data display, and conclusion drawing. The findings reveal that overlapping authority among the Tanjungpinang FTZ Management Agency, local government institutions, and national licensing authorities has created institutional fragmentation. Weak inter-agency coordination, inconsistent implementation of the Online Single Submission (OSS) system, and regulatory ambiguities contribute to procedural complexity and uncertainty for investors. These challenges have reduced administrative efficiency, delayed investment realization, and weakened the competitiveness of the Tanjungpinang FTZ compared to other special economic zones. The study emphasizes the need for regulatory harmonization, clearer institutional authority, strengthened coordination mechanisms, and integrated licensing services to improve investment governance and enhance regional competitiveness.